Estrategias para la promoción de la sexualidad saludable en los adolescentes de la Parroquia Quiroga Cantón Cotacachi - Mediavilla, Andrea R. (2017)
This research work responds to the need to promote the knowledge and practice of healthy sexuality among adolescents in Quiroga, canton Cotacachi. The present research contributes to the scientific field, providing reliable statistical data about the problematic situation of the early sexual practice in Quiroga. It also makes significant contributions to the area of health and education as it presents an effective tool for intervention in education for healthy sexuality of adolescents.